The Impact of Passive Smoking at Home on Respiratory Diseases : Results from the Indonesia 2001 National Survey Data - Djutaharta, Triasih; Ahsan, Abdillah; Tachman, Tata; Hendratno; Gilpin, Elizabeth (World Bank, Washington, DC, 2013)
This study uses raw data covering over 17,000 people from the 2001 National Socio-Economic Survey (NSES) and 2001 National Household Health Survey (NHHS), including 3621 children under 10 years of age, to investigate the relationship between respiratory diseases and exposure to secondhand cigarette smoke through living in a home where people smoke. An important finding is that children under 10 years of age who live in homes where 30 or more cigarettes are smoked each day are significantly more likely to have various respiratory diseases than children who live in smoke-free homes.